2012
DOI: 10.1111/apm.12001
|View full text |Cite
|
Sign up to set email alerts
|

Does JC virus have a role in the etiology and prognosis of Egyptian colorectal carcinoma?

Abstract: John Cunningham virus (JCV) encodes an oncogenic T-antigen, which is capable of interacting with key growth regulatory pathways. JCV definite role as causal agent of human cancer, still awaits final confirmation. The present study was conducted to assess the possible role of JCV in Egyptian colorectal carcinoma (CRC) and correlate the expression with the clinicopathological features and survival. JCV in situ hybridization (ISH) signals and large T antigen immunoreactivity were examined in 87 colonic specimens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…Sarvari et al, 2018;Haghi Navand et al, 2019) and five studies assessed the BK virus prevalence (Casini et al, 2005;Giuliani et al, 2008;Tseng et al, 2014;Jarzynski et al, 2017;Sarvari et al, 2018) Some studies had used several targets and diagnostic methods (Enam et al, 2002;Hori et al, 2005;Lin et al, 2008;Tsekov et al, 2011;Mou et al, 2012;Matalka et al, 2013;Tseng et al, 2014). One stydy used In Situ Hybridization (ISH) (Samaka et al, 2013), one study used real time PCR(Polymerase Chain Reaction) (Tsekov et al, 2011) and others used PCR, nested-PCR or Immunohistochemistry (IHC), (Enam et al, 2002;Casini et al, 2005;Hori et al, 2005;Theodoropoulos et al, 2005;Goel et al, 2006;Giuliani et al, 2008;Jung et al, 2008;Lin et al, 2008;Niv et al, 2010a;Niv et al, 2010b;Ramamoorthy et al, 2011;Tsekov et al, 2011;Mou et al, 2012;Coelho et al, 2013;Matalka et al, 2013;Ripple et al, 2014;Sinagra et al, 2014;Ksiaa et al, 2015;Jarzynski et al, 2017;Toumi et al, 2017;Sarvari et al, 2018;Haghi Navand et al, 2019). Most of the studies targeted DNA and T antigen (TAg) from the samples in order to diagnose the viruses …”
Section: Discussionmentioning
confidence: 99%
“…Sarvari et al, 2018;Haghi Navand et al, 2019) and five studies assessed the BK virus prevalence (Casini et al, 2005;Giuliani et al, 2008;Tseng et al, 2014;Jarzynski et al, 2017;Sarvari et al, 2018) Some studies had used several targets and diagnostic methods (Enam et al, 2002;Hori et al, 2005;Lin et al, 2008;Tsekov et al, 2011;Mou et al, 2012;Matalka et al, 2013;Tseng et al, 2014). One stydy used In Situ Hybridization (ISH) (Samaka et al, 2013), one study used real time PCR(Polymerase Chain Reaction) (Tsekov et al, 2011) and others used PCR, nested-PCR or Immunohistochemistry (IHC), (Enam et al, 2002;Casini et al, 2005;Hori et al, 2005;Theodoropoulos et al, 2005;Goel et al, 2006;Giuliani et al, 2008;Jung et al, 2008;Lin et al, 2008;Niv et al, 2010a;Niv et al, 2010b;Ramamoorthy et al, 2011;Tsekov et al, 2011;Mou et al, 2012;Coelho et al, 2013;Matalka et al, 2013;Ripple et al, 2014;Sinagra et al, 2014;Ksiaa et al, 2015;Jarzynski et al, 2017;Toumi et al, 2017;Sarvari et al, 2018;Haghi Navand et al, 2019). Most of the studies targeted DNA and T antigen (TAg) from the samples in order to diagnose the viruses …”
Section: Discussionmentioning
confidence: 99%
“…Additionally 240 adenoma tissues were analyzed and compared with 257 normal tissues from healthy controls: JCPyV DNA was found in 77 adenoma (32.1%) and 48 normal (18.7%) tissues, respectively (Table 2 ) [ 115 , 127 , 128 ]. The expression of the JCPyV proteins was analyzed only in 4 studies [ 126 , 130 – 132 ] and it has been observed that the early T-Ag protein was present in 9 out of 172 (5.2%) colorectal cancer or adenoma tissues and in 7 out of 38 (18.4%) adjacent noncancerous tissues or normal tissues from healthy controls (Table 3 ). Rollison and colleagues and Lundstig and colleagues collected blood samples from colorectal patients, and healthy controls and found a total of 210 (41.3%), and 179 (38.4%) seropositive subjects out of 509 colorectal patients, and 466 and healthy subjects (Table 3 ) [ 130 , 131 ].…”
Section: Jcpyv and Human Colorectal Cancermentioning
confidence: 99%
“…To date, no conclusive prospective studies supporting a causal association between JCPyV infection and cancer development in humans have been conducted. Several case-control studies, sometimes nested within cohort studies, have been conducted to establish the association between JCPyV seropositivity and specific human tumor types, including colorectal cancer 155 - 161 , lymphoma 162 , 163 , central nervous system tumors 164 165 - 166 , esophageal carcinoma 167 , carcinoma of the bladder 168 , and prostate cancer 169 . These results should be interpreted with caution since anti-JCPyV antibodies may persist for decades, indicating previous exposure to the agent but not viral reactivation.…”
Section: Introductionmentioning
confidence: 99%